Effect of methylglyoxal on multidrug-resistant Pseudomonas aeruginosa - Hayashi, Katsuhiko; Fukushima, Aiko; Hayashi-Nishino, Mitsuko; Nishino, Kunihiko (Frontiers in Microbiology, 2014)
Honey has a complex chemistry, and its broad-spectrum antimicrobial activity varies with floral source, climate, and harvesting conditions. Methylglyoxal was identified as the dominant antibacterial component of manuka honey. Although it has been known that methylglyoxal has antibacterial activity against gram-positive bacteria, including methicillin-resistant Staphylococcus aureus and vancomycin-resistant Enterococcus, there is not much information describing its activity against gram-negative bacteria. In this study, we report the effect of methylglyoxal against multidrug-resistant Pseudomonas aeruginosa (MDRP) using 53 clinically isolated strains. We also assessed the effect of deleting the five multidrug efflux systems in P. aeruginosa, as well as the efflux systems in Escherichia coli and Salmonella enterica serovar Typhimurium, on MICs of methylglyoxal. Our results indicate that methylglyoxal inhibits the growth of MDRP at concentrations of 128–512 μg/ml (1.7–7.1 mM) and is not recognized by drug efflux systems.